An analysis of risk-taking behavior for public defined benefit pension plans - Mohan, Nancy; Zhang, Ting (Journal of Banking & Finance, 2014)
This paper presents the first comprehensive study on the determinants of public pension fund investment risk and reports several new important findings. Unlike private pension plans, public funds undertake more risk if they are underfunded and have lower investment returns in the previous years, consistent with the risk transfer hypothesis. Furthermore, pension funds in states facing fiscal constraints allocate more assets to equity and have higher betas. There also appears to be a herding effect in that CalPERS equity allocation or beta is mimicked by other pension funds. Finally, our results suggest that government accounting standards strongly affect pension fund risk, as higher return assumptions (used to discount pension liabilities) are associated with higher equity allocation and portfolio beta.